THE CANDIDATE ENGINEERING ACADEMIC DEGREE REQUIRED NOW - A. I. Rudskoy; A. I. Borovkov; P. I. Romanov; K. N. Kiseleva (Moscow Polytechnic University, 2017)
The President of Russia Vladimir Putin suggested to launch a large-scale system program aimed at the development of the economy of a new technological generation, the so-called digital economy. The program implementation is impossible without the engineering personnel of high qualification, which is able to create the technologies of the world level in the shortest possible time. When improving the domestic system of training personnel of higher qualification it may be useful to analyze an experience ofprofessional doctorate training in the UK and other Anglo-Saxon countries of the world where professional doctoral programs focus rather on industry or business than on academic sphere.The article analyzes the world experience in implementation the programs of professional doctorate training and gives suggestions for using this experience in Russia by integrating the similar programs into the current system of scientific-pedagogical personnel training in postgraduate study.